GREEN SYNTHESIS OF SILVER NANOPARTICLES (AgNPS) CONTAINING COMBINATION OF AQUEOUS EXTRACT OF Capsicum annuum L. AND SAFFRON: BIOSYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL ACTIVITY - Erna Fitriany; Andri Priyoherianto; Masfah Raudlotus S.; Indah Tri Lestari; Fahmi Ardianti Purnawiranita (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Silver nanoparticles or Ag-Nanoparticles (AgNPs), which exhibit antimicrobial and biomedical activities, have many benefits in the health sector. AgNPs can be prepared using chemicals such as sodium borohydride (NaBH4). The green synthesis of AgNPs is an environmentally friendly alternative and is cost-effective. Capsicum annuum L. combined with saffron extract was used to synthesize the AgNPs. The biosynthesis, characterization, and antibacterial activity of AgNPs were studied in this study. The synthesized AgNPs were characterized by UV-visible (UV-Vis) spectroscopy, Fourier-transform Infrared Spectroscopy (FTIR), and particle size analysis (PSA). The formation of AgNPs was confirmed by optical performance using UV-VIS spectroscopy, which showed a peak of AgNPs at 407 nm. Capsicum annuum L. combined with saffron extract containing C-H, C-N, and C=O groups. Particle size was characterized using PSA, measuring 37.74 nm with an average SD Â±22.10. Capsicum annuum L. combined with the saffron extract showed effective antibacterial activity. Â Keywords: Green Synthesis, AgNPs, Capsicum annuum L, Saffron